Learning Citizenship Differently: Feminist Schools and the Making of Political Subjects - Annisa Sabrina Hartoto (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2025)
This article examines how feminist education reconfigures political subjectivity and citizenship in Indonesia through an ethnographic study of the Sekolah Kepemimpinan Feminis (SKF), a feminist leadership school run by Solidaritas Perempuan in Makassar. In contrast to state-led civic education, which reinforces moral obedience, nationalist duty, and gendered respectability, SKF cultivates a different civic imagination—one grounded in feminist critique, affective labour, and collective struggle. Drawing on participant observation and life history interviews with participants and organisers, this article explores how young women from diverse and marginalised backgrounds relearn their place in the world through shared reflection, storytelling, and political engagement. It argues that SKF functions as a citizenship laboratory: a pedagogical and political space where new forms of subjectivity are enacted through the rejection of normative gender roles and the development of feminist consciousness. Through informal, relational, and embodied practices, participants learn to link personal experience with structural injustice and build alternative modes of belonging. This study contributes to debates on feminist pedagogy, youth activism, and alternative education by demonstrating how feminist schools offer insurgent spaces for imagining citizenship beyond the boundaries of the state.